Generation of endogenous soluble PD-1 as a potential therapeutic strategy for cancer treatment - Wahid, Mussarat (2019)
The Programmed cell death (PD-1) pathway is an immunoinhibitory T cell pathway that is involved in maintaining peripheral T cell tolerance and regulation of inflammation. PD-1 binds to its ligand, PD-L1 which is expressed normally on a variety of cells and aberrantly on cancer cells. Binding of PD-1 to PD-L1 is a dominant immune checkpoint pathway operative in the tumour microenvironment; its normal function is to control immune homeostasis but is exploited by the cancer cells to evade immune attack. Targeting this pathway by blocking antibodies (nivolumab and pembrolizumab) has given impressive anti-cancer responses in patients with a range of cancer types. Blocking of these pathways have successfully shown to restore the function of exhausted T cells.